APLIKASI KAIDAH KEBAHASAAN BAHASA INDONESIA DALAM TAJUK BERITA SURAT KABAR SEBAGAI KONSUMSI INFORMASI PUBLIK DI KOTA MAKASSAR - Juanda, Juanda; Azis, Azis (Jurnal Ilmu Budaya, 2019)
The purpose of this research is to determine the use of Indonesian standard in headline news in newspaper discourse relate to the diction/vocabulary; writing; sentence structure; and use of vernacular languages, and foreign terms. This research focuses on the use of Indonesian standard in the headline newspaper of Harian Fajar newspaper. This research is a qualitative method of content analysis. The source data are from daily Harian Fajar Tajuk Newspaper. The result showed that the diction or vocabulary in the discourse of headline news used language hyperbole, oxymoron, and personification. The writing word such as acronyms, technical terms. The majority of the style of language used by the writer is hyperbole. The writer used many acronyms. The technical terms are dominated by English vocabulary. The writing is not appropriate, namely: the writing of the word, the error in the writing of letters, capital letters, the compound word, and preposition di. Particle that often arise in the writing errors is pun. These of punctuation is not appropriate, namely the use of comma, in the details of words and the use of hyphen in the decoding in the words. The sentence structure in the form of the head line news of Harian Fajar is to be a symbol (+), proverbs, advice, and imperative sentence. The ambiguous sentence, conjunction occur due to improving is not appropriate, ie: untuk kemudian, padahal agar, mesti, sehingga, jadi, karena, disebabkan oleh, dan bahwa. Many sentences found in the data are ineffective. One of the reasons is became of a combination of the two ideas in a sentence. There is a tendency of the writer to write down his words affix me- writer the based words only and many sentences do not have clear subject.